2018
DOI: 10.5114/wiitm.2018.72646
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic effects of skin-crease camouflage incision versus longitudinal incision following carotid endarterectomy.

Abstract: IntroductionDespite the increasing use of carotid angioplasty and stenting (CAS), carotid endarterectomy (CEA) nonetheless remains a more medically beneficial method of treatment for carotid artery stenosis. Therefore, one possibility for progress within this procedure may be to use minimally invasive carotid surgery, especially when the scar is in plain sight: the use of the natural wrinkles (skin crease) as a camouflage of the skin incision provides significant cosmetic improvements.AimTo compare the cosmeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…To decrease neurologic deficits and improve cosmetic effects, some centers have used minimal longitudinal incisions in a conventional manner, with or without sonographic assistance [2,6]. Furthermore, transverse incisions camouf laged in a skincrease have also been investigated [3,[7][8][9]. Studies of vertical incisions in CEA have shown that a minimal incision causes fewer local neurologic complications than a conventional incision, but no statistical differences have been observed in the incidence of stroke and death [2,6,10].…”
Section: Discussionmentioning
confidence: 99%
“…To decrease neurologic deficits and improve cosmetic effects, some centers have used minimal longitudinal incisions in a conventional manner, with or without sonographic assistance [2,6]. Furthermore, transverse incisions camouf laged in a skincrease have also been investigated [3,[7][8][9]. Studies of vertical incisions in CEA have shown that a minimal incision causes fewer local neurologic complications than a conventional incision, but no statistical differences have been observed in the incidence of stroke and death [2,6,10].…”
Section: Discussionmentioning
confidence: 99%
“…The POSAS SDs in studies previously published on carpal tunnel release and carotid endarterectomies range from 1.0 to 11.0. 19 , 20 To detect a mean difference in POSAS score of 10 points (SD = 8) with a two-sided significance level of 5% and power of 80% with equal allocation to two arms required 12 patients in each arm of the trial.…”
Section: Methodsmentioning
confidence: 99%
“…3B ). 11 , 13) Kazimierczak et al 14) reported a randomized study of camouflage (transverse) incision versus longitudinal incision. Although no significant difference in mortality or morbidity was seen between groups, scar assessment scale score was significantly better in patients with camouflage incision than in patients with longitudinal incision.…”
Section: Skin Incisionmentioning
confidence: 99%
“…Although no significant difference in mortality or morbidity was seen between groups, scar assessment scale score was significantly better in patients with camouflage incision than in patients with longitudinal incision. 14) However, if stenosis of the ICA extended to a high position, the transverse incision was limited to exposing the distal side of the ICA, and most surgeons use an extended longitudinal skin incision to improve distal ICA exposure ( Fig. 3C ).…”
Section: Skin Incisionmentioning
confidence: 99%